(untitled) (Journal of the College of Basic Education, 2022)
The effect of relaxation exercises on some psychological alterations and aiming precision with air weapons (the gun) Experimental Research Researcher: Agharied Salim The aims of this research consist of acknowledging the effect of Relaxation alterations in the athletes of the rifle national team, aside from acknowledging the effect of relaxation exercises on aiming precision on the athletes of the riflery national team (the rifle). The assumption of this research: There are assumptions of statistical indication between the two before and after experiment on all alterations and for the benefit of the after experiment. The sample of this research consisted of (10) pro athletes in rifelry. And In the light of the research results we have come to the following: 1. The relaxation exercises lead to an improvement in the psychological alterations for the research sample. 2. Relaxing exercises lead to improvement in aiming precision for the research sample. The research recommends the necessity of relaxat